Pengaruh Keamanan Transaksi, Kemudahan Transaksi Dan Kualitas Informasi Produk Terhadap Keputusan Pembelian Secara Online Pada Konveksi I_Luup Production Home Kota Metro - Mega Selviana; Nani Septiana; Selamet Fuadi (Universitas Muhammadiyah Metro, 2025)
One effective strategy for starting a local business is to use content that encourages users to visit a product's website or store, usually through online advertising on the website's media platform that promotes the product. With a significant increase in internet usage, it can have a positive impact on purchasing decisions. Purchasing decisions themselves are part of consumer behavior, where respondents have a tendency to act before finally making a purchase decision. Ease of online transactions as a simple ordering process, diverse and easy payment methods, a purchase process that provides benefits and convenience, and fast and accurate delivery of goods. The existence of this ease of transaction can provide a sense of security to consumers and potentially increase the number of customers. To find out whether Transaction Security directly affects purchasing decisions at Metro City Convection I_Luup Production Home. To find out whether the Ease of Transaction directly affects the purchase decision at the Metro City I_Luup Production Home Convection. To find out whether the quality of product information directly affects purchasing decisions at Metro City I_Luup Production Home Convection. To find out whether transaction security, ease of transaction and quality of product information together directly affect purchasing decisions at Metro City I_Luup Production Home Convection. The sample of this study was all 60 consumers of Convection I_Luup Production Home Metro City. Data collection using interviews, questionnaires and data analysis using Validity Test, Reliability Test, Normality Test, Regression Linearity and Meaningfulness Test, Homogeneity Test and Path Analysis using SPSS program. The results show that there is a positive and significant influence of Transaction Security on the Quality of Product Information. There is a positive and significant influence of ease of transaction on the quality of product information. There is a positive and significant influence of Transaction Security on Purchasing Decisions. There is a positive and significant influence of ease of transaction on purchasing decisions. There is a positive and significant influence of product information quality on purchasing decisions.